The Teacher Belief and Teacher Praxis in the Implementation of the Merdeka Curriculum in Class II at SD Negeri 91 Palembang - Dela Dwi Oktalena; Agra Dwi Saputra; Faisal (The Future of Education Journal, 2025)
This study aims to identify teachers' beliefs and analyze their praxis in implementing the Merdeka Curriculum, as well as to examine the impact of teacher beliefs on their praxis in the implementation of the Merdeka Curriculum in Class II at SD Negeri 91 Palembang. The research design used is a descriptive qualitative method. Data collection techniques include interviews, observations, and documentation. The data sources in this study consist of the school principal, the Class II homeroom teacher, and several Class II students. The collected data were analyzed through stages of data reduction, data presentation, and conclusion drawing. The results show that teacher beliefs regarding the Merdeka Curriculum implementation indicate that teachers generally have a positive belief in understanding the Merdeka Curriculum, although challenges still exist, such as limited understanding of the essence of the Merdeka Curriculum, a lack of continuous training, and difficulties in developing assessments that align with the principles of differentiated learning. Teachers' praxis in implementing the Merdeka Curriculum shows efforts to apply differentiated and project-based learning, but it has not been fully consistent. Teachers still tend to use conventional methods and lack confidence in the new approaches.